2015
DOI: 10.1007/s10067-015-3119-3
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with Bosentan and Sildenafil improves Raynaud’s phenomenon and fosters the recovery of microvascular involvement in systemic sclerosis

Abstract: The aim of this study was to evaluate in systemic sclerosis (SSc) retrospectively the effect of Bosentan and Sildenafil and their combination on Raynaud's phenomenon (RP), function, and capillaroscopic patterns. One hundred and twenty-three SSc patients (mean age ± sd, 57.69 ± 14.07 years) were retrospectively evaluated and divided into two groups according to American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) classification score: group 1 score < 10, group 2 score > 10. Each gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 23 publications
1
24
0
2
Order By: Relevance
“…The aforementioned drugs were distributed in two compartments of the tablet of either immediate or sustained release. Similarly to hypertension, clinical reports, not only on PAH but also on Raynaud's disease, suggest that the combination of PDE-5 inhibitors and BOS can improve the effectiveness of therapy; therefore, the thermal properties of SIL, TA and BOS are investigated in details in the present study (6,11). Thermal decomposition of sildenafil citrate was already described by Melnikov et al (23).…”
Section: Thermal Propertiesmentioning
confidence: 84%
See 1 more Smart Citation
“…The aforementioned drugs were distributed in two compartments of the tablet of either immediate or sustained release. Similarly to hypertension, clinical reports, not only on PAH but also on Raynaud's disease, suggest that the combination of PDE-5 inhibitors and BOS can improve the effectiveness of therapy; therefore, the thermal properties of SIL, TA and BOS are investigated in details in the present study (6,11). Thermal decomposition of sildenafil citrate was already described by Melnikov et al (23).…”
Section: Thermal Propertiesmentioning
confidence: 84%
“…TA (6). Furthermore, it has been reported that BOS combined with SIL has been found effective in the therapy of Raynaud's phenomenon (11).…”
Section: Introductionmentioning
confidence: 95%
“…PDE5 inhibitors potentiate NO‐dependent vasodilation by prolonging the elevation of cGMP. Sildenafil is under active study in a variety of conditions associated with microvascular dysfunction 31, 32, 33, 34. Sildenafil's endothelial repair properties have been studied in several conditions associated with chronic diabetes 34.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, a significant improvement of capillaroscopic findings was observed in SSc patients treated with bosentan alone or with a combination of bosentan and sildenafil after 3 and 6 months with reduction of the “late” and “active” phase “scleroderma” pattern and an increase of the “aspecific” findings or “early” pattern . Thus, the “reverse” order of appearance of the capillaroscopic changes is obviously possible and is currently observed after treatment with immunosuppressive drugs, hematopoietic stem cell transplantation and bosentan …”
Section: Discussionmentioning
confidence: 92%
“…21 Thus, the "reverse" order of appearance of the capillaroscopic changes is obviously possible and is currently observed after treatment with immunosuppressive drugs, hematopoietic stem cell transplantation and bosentan. [21][22][23][24] Further research on precise interpretation of the dynamics of capillaroscopic changes in SSc is necessary eg, could "reverse" ap-…”
Section: Patientmentioning
confidence: 99%